The Effect of Combined Aren Palm Sap and Molasses as Carbon Sources on the Growth and Survival of Vannamei Shrimp (Litopenaeus vannamei) - Helmiana, Baiq; Lestari, Dewi Putri; Mulyani, Laily Fitriani (Jurnal Biologi Tropis, 2025)
Vannamei shrimp (Litopenaeus vannamei) is one of the most widely cultivated aquaculture commodities due to its high market demand and ability to grow intensively. However, intensive systems often generate environmental issues, especially from excess feed and ammonia waste. This study aimed to determine the best combination of aren palm sap and molasses as organic carbon sources in fermented feed to improve the growth and survival of L. vannamei. The research was conducted over 45 days using an experimental method and a completely randomized design (CRD) consisting of six treatments and three replications, totaling 18 experimental units. The treatments included: P1 (control feed), P2 (feed + 10 ml/kg aren sap), P3 (feed + 10 ml/kg molasses), P4 (5 ml/kg aren sap + 5 ml/kg molasses), P5 (2.5 ml/kg aren sap + 7.5 ml/kg molasses), and P6 (7.5 ml/kg aren sap + 2.5 ml/kg molasses). The research included feed fermentation, shrimp rearing, water quality monitoring, and sampling. The best results were observed in treatment P5, which yielded the highest protein content in feed (32.98%), total bacteria (1,249,000 CFU), absolute weight gain (4.48 g), length gain (5.8 cm), specific growth rate (7.84%/day), feed efficiency (79.88%), and lowest feed conversion ratio (1.25). The combination of 2.5 ml/kg aren sap and 7.5 ml/kg molasses is recommended to enhance shrimp growth and feed utilization without negatively impacting water quality.